Reisolation of Ehrlichia canis from blood and tissues of dogs after doxycycline treatment. - Iqbal, Z (1994)
We present evidence that supports the carrier status of dogs experimentally infected with Ehrlichia canis after treatment with doxycycline. Canine ehrlichiosis was induced in five dogs by intravenous inoculation with E. canis-infected DH82 cells. All animals developed mild clinical signs of transient fever, body weight loss, thrombocytopenia, and increased gamma globulin levels in plasma. An indirect fluorescent-antibody test (IFA) revealed that all dogs had seroconverted (titer, 5,120) by day 10 postinoculation (p.i.). E. canis was reisolated from blood samples collected at intervals throughout the 2-month period p.i. Doxycycline was administered orally once daily at 10 mg/kg of body weight per day for 1 week starting at 2 months p.i. Following treatment, gamma globulin levels in plasma were decreased. At necropsy on days 54 to 59 after the start of treatment, spleen, liver, kidney, and lymph nodes were collected for E. canis culture and histopathologic examination. Although the dogs did not show significant clinical signs during or after treatment with the antibiotic, E. canis was reisolated from the blood and tissue samples of three of five dogs. A 16-fold reduction in IFA titer was noted in two dogs which were negative for E. canis reisolation at day 49 after the start of treatment, whereas a zero- to fourfold reduction in IFA titer was seen in the remaining three dogs. Western immunoblot reactions to higher-molecular-size E. canis antigens in the sera of two dogs which were negative for E. canis on blood culture decreased, whereas they remained continuously high or only transiently decreased for the duration of the study for antigens in the sera of three dogs from which E. canis was reisolated. Histopathologically, prominent plasmacytosis in the kidney cortex was present in three dogs from which E. canis was reisolated, whereas the kidney cortices of two dogs had moderate to minor plasmacytosis. These findings pose questions regarding the efficacy, dosage and duration of doxycycline treatment in dogs with E. canis infection. In addition, it was shown that IFA and Western immunoblotting may aid in assessing the efficacy of antibiotic therapy when definitive reisolation procedures are not readily available.